Assessing electronic immunization registries: the Pan American Health Organization experience - M. Carolina Danovaro-Holliday; Marcela P. Contreras; Dalys Pinto; Ida Berenice Molina-Aguilera; Diana Miranda; Odalys García; Martha Velandia-Gonzalez (Pan American Health Organization, 2019)
Objective. To develop a methodology to assess electronic immunization registries (EIRs) in low- and middle-income countries (LMICs) in Latin America and the Caribbean. Methods. A team from the Immunization Unit at the Pan American Health Organization (PAHO) reviewed existing methodologies to evaluate health information systems, particularly the Performance of Routine Information System Management (PRISM) framework and methodologies used to assess information systems. In 2014, the PAHO team convened a small working group to develop an evaluation approach to be added to the existing World Health Organization immunization data quality self-assessment (DQS) tool. The resulting DQS with an added EIR component was named "DQS Plus." The DQS Plus methodology was used in Panama in May 2014 and in Honduras in November 2015. Results. The DQS Plus tool proved feasible and easy to implement in Panama and Honduras, including by not adding much time or resources to those needed for a usual DQS. The information obtained from the DQS Plus assessment was practical and helped provide health authorities with recommendations to update and improve their EIR, strengthen the use of the registry, and enhance the data the assessment produced, at all levels of the health system. These recommendations are currently being implemented in the two countries. Conclusions. The DQS Plus proved to be a practical and useful approach for assessing an EIR in an LMIC and generating actionable recommendations. Further work on defining operational and related EIR functional standards in LMICs will help develop an improved EIR assessment tool for Latin America and the Caribbean, and potentially elsewhere.